MOLECULAR DOCKING STUDIES AND BIOACTIVITY OF VARIOUS BENZILIC ACIDS AND ITS ANALOGS - R, Sudha; Kanakam, Charles C; G, Nithya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Various benzilic acids and its analogs have been synthesized using the protocol, obtain good to exceptional yield and their biological activity, and its docking studies have been discussed. Methods: Molecular docking studies were performed by discovery studio - LibDock docking program. To determine the cytotoxic effects, we used an MTT viability assay. Results: The results showed that cell growth is significantly lower in extract treated cells compared to untreated control. The effect of inhibition of cell growth was shown in different concentration dosages for cytotoxic, antibacterial, and antioxidant activity in vitro. Conclusion: From the antibacterial results prove that the synthesized compounds showed the potential activity. These remarks may give the encouragement of further development of our research in this field. The antioxidant activity was also performed for the compound benzilic acid and its substituted analogs.